Effects of performance based financing on facility autonomy and accountability: Evidence from Zambia - Chitalu Miriam Chama-Chiliba; Peter Hangoma; Collins Chansa; Mulenga Chonzi Mulenga (Elsevier, 2022)
Several low and lower- middle income countries have been using Performance-Based Financing (PBF) to motivate health workers to increase the quantity and quality of health services. Studies have demonstrated that PBF can contribute to improved health service delivery and health outcomes, but there is limited evidence on the mechanisms through which PBF can necessitate changes in the health system. Using difference-in-difference and synthetic control analytical approaches, we investigated the effect of PBF on autonomy and accountability at service delivery level using data from a 3-arm cluster randomised trial in Zambia. The arms consisted of PBF where financing is linked to outputs in terms of quality and quantity (intervention 1), input financing where funding is fully provided to finance all required inputs regardless of performance (intervention 2), and the current standard of care where there is input financing but with possible challenges in funding (pure control). The results show an increase in autonomy at PBF sites compared to sites in the pure control arm and an increase in accountability at PBF sites compared to sites in both the input-financing and pure control arms. On the other hand, there were no effects on autonomy and accountability in the input-financing sites compared to the pure control sites. The study concludes that PBF can improve financial and managerial autonomy and accountability, which are important for improving health service delivery. However, within the PBF districts, the magnitude of change was different, implying that management and leadership styles matter. Future research could examine whether personal attributes, managerial capacities of the facility managers, and the operating environment have an effect on autonomy and accountability.